Screening of snake gourd genotypes for low infestation against semilooper, Anadevidia peponis F. (Lepitoptera: Noctuidae) - Devi, N. Deepa; Jayaraj, J. (ENTOMON, 2017)
Fifty snake gourd genotypes were evaluated to screen for low infestation against semilooper during 2011-2012 under field condition. The low infestation of semilooper was observed in Kulithalai local short, Kumbakonam local short, Kumbakonam local long, Madurai local long and PKM-1 types (43 to 49.70 larvae per vine). While the genotypes viz., IC418478, IC411877, IC411878 and IC410160 recorded a higher semilooper infestation (91.0, 84.7, 77.0 and 72.0 larvae per vine respectively) and the yields recorded from these genotypes were significantly lower than the local types.Â 